An Analysis of Needs and Inclusive Education Service Strategies for Slow Learners at SD Negeri 1 Glagah - Dyan Ikawati Novitasari; Salamah Salamah; Choiriyah Widyasari (The Future of Education Journal, 2026)
This study examines the needs analysis and inclusive education service strategies for slow learners at SD Negeri 1 Glagah. The underlying issue of this research is that inclusive education services have been implemented through the admission of students with special needs into regular classrooms; however, learning services still require more systematic individualized adjustments. This study aims to identify the learning needs of slow learners, describe the current condition of inclusive education services, and formulate appropriate service strategies to support adaptive learning. This research employed a descriptive qualitative approach with a case study design. The primary subject of the study was one slow learner student, while supporting informants included the classroom teacher, school principal, and parents. Data were collected through observation, semi-structured interviews, and documentation, and then analyzed through data condensation, data display, and conclusion drawing. The findings reveal that the student was able to recognize numbers from 1 to 20 and perform simple addition and subtraction, but still experienced difficulties in understanding word problems, maintaining attention, and completing tasks independently. Socially, the student was able to interact with peers and follow teachers’ instructions. Inclusive education services at the school were still predominantly classical in nature, and the Individualized Education Program (IEP) had not yet been systematically developed. The recommended strategies include the development of an Individualized Education Program, step-by-step instruction, the use of concrete learning media, simple instructions, adaptive evaluation, and collaboration among teachers, schools, and parents.